FAKTOR UTAMA TERJADINYA PERKAWINAN DI BAWAH UMUR DI DESA KUALA LUMPUR KECAMATAN PAGUYAMAN - PUSI, TINSIAWATY R.; KASIM, NUR M.; BAKUNG, DOLOT ALHASNI; KADIR, MUHAMAD KHAIRUN KURNIAWAN (GANEC SWARA, 2024)
Marriage under the age has become a national phenomenon, culture has become a factor that has a big influence on the pattern of life in society, which is included in marriage under the age. The number of underage marriages is still rampant in Kuala Lumpur. The existence of quite significant figures provides an illustration that the existing legislative regulations are not effective enough in becoming reference regulations in society. This research aims to find out the main factors in the occurrence of underage marriages in Desa Kuala Lumpur, Paguyaman District. This research uses the Juridical Empirical type of research. The results of this research found that underage marriages that occurred in Kuala Lumpur, Paguyaman District, Boaleimo Regency, were classified as disharmonious households, due to several problems experienced by couples in underage marriages. These include a lack of awareness between partners regarding household duties, the task of looking after children which is assigned to one party, economic and work problems as well as communication patterns that lack mutual respect